Characteristics of EGRET blazars in the VLBA Imaging and Polarimetry Survey (VIPS) - Taylor, G; Healey, SE; Helmboldt, J; Tremblay, S; Fassnacht, C; Walker, R; Sjouwerman, L; Pearson, T; Readhead, A; Weintraub, L; Gehrels, N; Romani, R; et al. (Institute of Physics Publishing, 2007)
We examine the radio properties of EGRET-detected blazars observed as part of the VLBA Imaging and Polarimetry Survey (VIPS). VIPS has a flux limit roughly an order of magnitude below the MOJAVE survey and most other samples that have been used to study the properties of EGRET blazars. At lower flux levels, radio flux density does not directly correlate with gamma-ray flux density. We do find that the EGRET-detected blazars tend to have higher brightness temperatures, greater core fractions, and possibly larger than average jet opening angles. A weak correlation is also found with jet length and with polarization. All of the well-established trends can be explained by systematically larger Doppler factors in the gamma-ray-loud blazars, consistent with the measurements of higher apparent velocities found in monitoring programs carried out at radio frequencies above 10 GHz. © 2007. The American Astronomical Society. All rights reserved.